2022
DOI: 10.3390/pharmaceutics14061298
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a Physiologically Based Pharmacokinetic and Pharmacodynamic Model for Tegoprazan and Its Metabolite: Application for Predicting Food Effect and Intragastric pH Alterations

Abstract: A physiologically based pharmacokinetic/pharmacodynamic (PBPK/PD) model for tegoprazan and its major metabolite M1 was developed to predict PK and PD profiles under various scenarios. The PBPK model for tegoprazan and M1 was developed and predicted using the SimCYP® simulator and verified using clinical study data obtained after a single administration of tegoprazan. The established PBPK/PD model was used to predict PK profiles after repeated administrations of tegoprazan, postprandial PK profiles, and intraga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…The major metabolic pathway of tegoprazan is in the liver, and the kidney excretes a negligible amount [ 2 , 3 ]. Both in vitro and clinical results have elucidated that tegoprazan is a potential substrate of cytochrome P450 (CYP) 3A4 [ 2 , 3 , 4 , 5 , 6 ]. An in vitro study reported that ketoconazole, a strong inhibitor of CYP3A4, significantly inhibited the metabolism of tegoprazan in human liver microsomes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The major metabolic pathway of tegoprazan is in the liver, and the kidney excretes a negligible amount [ 2 , 3 ]. Both in vitro and clinical results have elucidated that tegoprazan is a potential substrate of cytochrome P450 (CYP) 3A4 [ 2 , 3 , 4 , 5 , 6 ]. An in vitro study reported that ketoconazole, a strong inhibitor of CYP3A4, significantly inhibited the metabolism of tegoprazan in human liver microsomes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…When tegoprazan was coadministered with another potent inhibitor of CYP3A34 (clarithromycin) in a clinical study, the maximum concentration ( C max ) and area under the concentration curve ( AUC ) during one dosing interval in the steady state of tegoprazan were increased 2.2-fold and 2.7-fold, respectively, compared with the administration of tegoprazan alone [ 6 ]. In addition to CYP3A4, it has been reported that tegoprazan is metabolized partly by CYP2C19 [ 2 , 3 , 4 ]. In the presence of recombinant CYP3A4 and CYP2C19, the intrinsic clearance of tegoprazan was 0.86 and 0.61 µL/min/pmol protein, respectively [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations